PERAN ASOSIASI PENDIDIK DAN PENGEMBANG BAHASA MANDARIN DI INDONESIA (APPBMI) DALAM PENGEMBANGAN BAHASA MANDARIN DI YOGYAKARTA (PENGAMATAN APPBMI DPD DIY) - , RINA HIDAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
APPBMI is an association focuses on increasing Chinese Language teachers and teaching methods level in Indonesia. APPBMI has members consisting of APPBMI DPD West Java, Banten, Jakarta, South Sulawesi, Surabaya and Yogyakarta. APPBMI DPD DIY has several activities to increase teaching quality and jointly to organize Chinese training class.